Mathematical models in biology - Edelstein-Keshet, Leah (McGraw-Hill, 1987)
The book discusses models into three broad categories: discrete, continous, and spatially distributed. The first describes populations that reproduce at fixed intervals; the second pertains to processes that may be viewed as continous in time; the last treats systems for which distribution over space is an important feature